ACTUAL PROBLEMS OF TERMINOLOGY - Avilova Klara Xudjayarovna (Western European Studies, 2024)
In this article, the author emphasized that the study of terminology problems is considered the most important task of linguistics, as well as that terminology is a part of vocabulary that is very sensitive to external influences. The author acknowledged that terminology as an independent scientific discipline gradually developed as a result of the autonomous development of separate scientific directions, and later emerged as a result of their synthesis.
Keywords: Study of terms; terminology; independent science